VOLCANIC ROCKS OF THE ISLAMIC ISLAND (IRAN) - Mykhailov, V.; Kryvdic, S.; Sharygin, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Neogene paleovolcan of the Islamic Island comprised by melaleucitite – feldspars leucitite – phonolite – trachyte series is situated on the coast of the Lake Urumia (Iran). Leucitites are composed of magnesium clinopyroxene, olivine, amphibole, Ва-Ті-phlogopite and feldspar. Clinopyroxenes of phonolite are enriched in Fe, phlogopites are depleted with Ba and Ti, feldspars are represented by Na-К-Bavarieties or anorthoclase. Leucitic rocks are enriched with Ba, Rb, Sr and have moderate content of Ce, Y, Zr and low Nb. At the diagram SO2 – MgO/(MgO+FeO) most of analyzes of leucitic rocks are plotted between fields of kamafugitic and tephrite-leucitic series, partly (enriched with SiO2) – in the field of lamprophyric series. At the diagram Al2O3–CaO most of analyzes correspond to tephrite-leucitic series, partly – to lamproitic. At the diagram of Zr-Nb leucitic rocks are plotted in the field of potassium rocks of subduction areas. They are characterized by low content of Nb, Ta, Ti. Unlike lamproite, leucitite of the Islamic Island has clayed (miaskite) composition. Their clinopyroxenes are more clayed then diopsides of lamproite. Clinopyroxenes and olivine of these rocks are more iron-rich than minerals of lamproite. These rocks are enriched in Ті and Ва, unlike typical lamproite. Presence of small amount of nepheline and sodalite, also distinguish them from typical lamproite. Leucite is similar to leucite from lamproite. Therefore, leucitic rocks of the Islamic Island are represented by series of non-plagioclase rocks, which are evolved from melaleucitite through leucitic phonolite to trachyte, involving quartz-bearing ones. Leucititic rocks of the Islamic Island are similar to transitional lamproite, associated with subduction in Phanerozoic mountain belts. Potassium alkaline rocks of Islamic Island with their mineralogical and geochemical peculiarities are similar to low-titanium lamproite. At the same time, leucitic rocks of the Islamic Island with their Ва-Ті-phlogopite and celsian feldspars might be treated as original formations. So leucitic rocks of the Islamic Island are similar to lamproites found in the folding belts characterized by occurrence of subduction.